What every EFL Instructor Needs to Know: Effective Implementation of Needs Analysis - Trendak-Suślik, Olga (Research in Language, 2023)
One of the first issues that any foreign language teacher needs to take into consideration prior to commencing on their language course is the implementation of a comprehensive learner needs analysis (NA) also referred to as needs assessment. Garnering information on, among others, students’ learning preferences, their previous learning experience or their goals is pivotal in order to design a course that would cater to students’ different needs and meet their expectations. A one-size-fits-all approach is not in line with the reality of language teaching in the 21st century, hence the need for the introduction of NA during language classes. The aim of the following article is to explore the area of needs analysis – examine its beginnings and further development; define its basic components and also investigate the different data-collection instruments language teachers have at their disposal. The article will also present the results of a pilot study exploring Polish teachers’ perspectives on the introduction of needs analysis in the foreign language classroom.